2018
DOI: 10.1097/rli.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Dynamic Contrast-Enhanced Magnetic Resonance Imaging Using Low-Dose Gadolinium

Abstract: These preliminary results suggest that DCE-MRI with a low GBCA dose distinguishes PCa from benign prostate tissue more effectively than does the standard GBCA dose, based on signal enhancement rate. Diagnostic accuracy is similar on qualitative assessment. Prostate cancer diagnosis may be feasible with DCE-MRI with low-dose GBCA. In addition, comparison of enhancement kinetics after low and high doses of contrast media may provide diagnostically useful information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The present results also suggest some clinical and diagnostic advantages for use of a low-dose contrast media DCE-MRI (39). The association between Gd-based contrast media administration and nephrogenic systemic fibrosis has been a concern for patients with renal failure.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The present results also suggest some clinical and diagnostic advantages for use of a low-dose contrast media DCE-MRI (39). The association between Gd-based contrast media administration and nephrogenic systemic fibrosis has been a concern for patients with renal failure.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, this was previously shown by comparing results from ultrafast DCE-MRI with those from DCE-CT with 120-mL Iohexol in 20 patients with prostate cancer (27). Previous work from this group showed that low-dose Gd contrast distinguishes prostate cancer from benign prostate tissue more effectively than a standard dose on the basis of the signal enhancement rate; this diagnostic accuracy is similar on qualitative assessments (39).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The GBCA dose (0.02 mmol/kg) was chosen based on both the numerical simulations and previous low-dose investigations. [44][45][46] In the simulations, the SD of the noise was defined as the averaged signal intensity of tumor over the nominal SNR at the standard dose, and was fixed for the other doses, leading to lower true SNR proportionate to the decreased signal intensity for lower dose. Based on Equations 5-7, the signal intensity drops faster when the dose decreases (as shown in Supporting Information Figure S4), causing increased bias and variation of the estimation.…”
Section: Discussionmentioning
confidence: 99%
“…With higher dose, stronger T 2 * effect may lead to more severe underestimation of R 1 and CA concentration. 45 Despite all of these factors, the in vivo study demonstrated that the kinetic parameters had strong correlation and good agreement between the LD-MT-DCE and SD-MT-DCE measurements, indicating that the MT-DCE technique using 20% dose has a similar ability to quantify vascular properties when compared with using standard dose. The kinetic parameters estimated by LD-MT-DCE for normal breast tissue and malignant, and benign tumors are in the range of published results.…”
mentioning
confidence: 91%